THE VENOM PATROL—AN ONLINE RESOURCE FOR IMPROVING HEALTH LITERACY AND FOR SNAKEBITE PREVENTION. (7th October 2012) - Winkel, K; Godinho, S; Lowe, R; Molyneux, P; Taylor, P; Wesley, N; Stone, M; Woolley, M
Abstract : Background: Science, health and general literacy are essential to fully address the determinants of Neglected Tropical Diseases (NTD) such as snakebite. However, such literacy standards are either not improving or falling in many countries. At the same time access to computers, the internet and smart phone technology has never been greater. Accordingly, we have developed a trans disciplinary collaboration to harness the power of ICT to further NTD prevention, and improve general literacy. Method: We have collaborated to create a venom-themed set of on-line teaching resources that is integrated with contemporary national educational pedagogy. Results: The Venom Patrol (http://www.venompatrol.org) consists of a website ('venompatrol.info') with more than 100 graphic-rich, interlinked pages with attached, high quality, documentary style video files and flash animations, together with photographs, downloadable pdfs, word documents and assessment profiles. It is a suite of teaching resources for use in primary and secondary schools and is complemented by a social networking and video conferencing site. The resource is focused around four habitats (arid desert, rainforest, suburban park and tropical coast) and was funded by the Australian Government for distribution to every Australian school. Conclusions: This is the first comprehensive venom-themed resource to have been produced for Australian Schools. It harnesses the potential of e-learning to stimulate student interest in science and health education and contributes this up-to-date knowledge to their families and communities. This may provide a template for other countries to develop NTD-related school and community knowledge transfer.